Effect of the provision of estimated waiting time on patient satisfaction with the Emergency Department: A randomized controlled trial - Khalid N. Almulhim; Lina A. AlMudayris; Zeyad K. Alshehri; Ahmed K. Alnawah; Danah A. Aljeri; Abdulaziz S. Hadadi (Journal of Family and Community Medicine)
BACKGROUND: Patient satisfaction is a quality measure that provides important details on the medical care provided. This study aimed to assess the effect of displaying “estimated waiting time” on patient’s satisfaction with emergency care. MATERIALS AND METHODS: This study included 190 patients from the Emergency Department (ED) of King Fahad Hofuf Hospital (KFHH) who were aged 18 and above and were triaged as 3 and above on the Canadian triage and acuity scale (CTAS). One hundred eighteen patients were selected as the entrance group, and 72 selected as the inside group that were further divided into intervention group (35) and control group (37); Intervention group received estimated waiting time. Two questionnaires were administered, first at the triage entrance and the second at the ED after being seen by the physician. Fischer’s exact test was applied to test for association between categorical variables, and Mann– Whitney U test was used to compare satisfaction scores between the groups. RESULTS: For the 118 patients at the triage entrance, 50% were aged 18-39 years, 62% were females, and 61% were triaged as category 3. One-third patients were willing to wait for 0-1 hour, and 28% described their symptoms as severe. Only 29.7% patients said they would wait until seen by doctor. No statistically significant difference in the level of satisfaction between patients who were provided with the estimated waiting time and those who were not (P=0.962). CONCLUSION: There were no statistically significant variations between the two groups’ preferences regarding patients’ awareness of their predicted waiting times. The results indicated that managing patients’ perceptions and expectations of waiting times effectively is inconsequential for the improvement of patient experience.